Real Time Formal Specification using VDM++ - Dürr, Eugène; Goldsack, Stephen; Katwijk, Jan van (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24437, 1996)
VDM++ is a formal Object Oriented Specification language, derived from VDM. It extends VDM by providing object-orientation, real-time as well as parallel features. The use of the language is supported by design guidelines and a tool set. The latter offers graphical representations, syntactic and semantic checking, pretty printing and code generation. In this paper we address the handling of particular real-time issues as supported by the language. An outline specification case study is included.